2023
DOI: 10.1186/s40900-023-00482-x
|View full text |Cite
|
Sign up to set email alerts
|

Community members’ experiences training as medical journal reviewers

Abstract: Purpose Although medical research dissemination is intended to benefit members of society, few members of society actually participate in the process of publishing findings. This study shares findings from community members’ (including patients and the public) experiences being trained as medical journal reviewers. Methods We analyzed findings from two focus group interviews of community reviewers (N = 29) to identify themes in their experiences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Community members need frequent and adequate communication as well as a full understanding of research requirements when they are engaged in research efforts. Research has found community members can be effectively trained to better understand, engage in research, and be amenable to learning [ 39 , 40 ]. Although most of the LHA training included topics on hypertension, much less focused on different types of study designs and distinctions between research approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Community members need frequent and adequate communication as well as a full understanding of research requirements when they are engaged in research efforts. Research has found community members can be effectively trained to better understand, engage in research, and be amenable to learning [ 39 , 40 ]. Although most of the LHA training included topics on hypertension, much less focused on different types of study designs and distinctions between research approaches.…”
Section: Discussionmentioning
confidence: 99%